Late Onset Graft Plasmacytoma-Like PTLD Presenting as Acute Hyperglycemia in a Kidney-Pancreas Transplant Recipient - P. Ventura-Aguiar; M. T. Cibeira; A. Martinez; M. Cuatrecasas; M. Aymerich; J. Ferrer; J. Blade; F. Diekmann; M. J. Ricart (Case Reports in Nephrology)
Allograft infiltration has been described in up to 20% of all patients with posttransplant lymphoproliferative disorder (PTLD), most representing EBV-positive B-cell lymphomas. Plasma cells are often observed in humoral rejection biopsies, but graft infiltration by plasmacytoma-like PTLD is rare. We report the case of a 54-year-old simultaneous pancreas-kidney transplant recipient (immunosuppression: OKT3, methylprednisolone, cyclosporine, and azathioprine), diagnosed with an IgG-kappa monoclonal gammopathy of undetermined significance eighteen years after transplant. Nine months later, pancreas allograft biopsy performed due to new-onset hyperglycemia (HgA1C 8.6%, C-peptide 6.15ng/mL and anti-GAD 0.9UI/mL) revealed a monotypic plasma cell infiltrate, CD19, CD79a, CD138 positive, with IgG-kappa light chain restriction, and EBV negative. PET-scan FDG uptake was limited to pancreas allograft. Tumor origin could not be established (using DNA microsatellite analysis). Despite treatment with bortezomib and dexamethasone, patient eventually died one month later. This is the first report of a late onset extramedullary plasmacytoma involving a pancreas allograft.